Rifabutin loaded floating gellan gum beads: In vitro and in vivo evaluation - Verma, A.; Pandit, J.K. (Academic Journals, 2011)
Rifabutin loaded floating gellan gum beads were prepared by ionotropic gelation in acidic medium. Buoyancy to the beads was attributed to the use of gas-generating agent, which produced an extremely porous internal structure lighter than gastric juice. Beads exhibited excellent buoyancy and remained buoyant up to 18 h. Drug incorporation efficiency of the beads was found to be dependent on the concentration of Ca++ and gellan gum whereas drug release was dependent only on Ca++ concentration. When administered orally to albino rats, beads floated on the gastric juice and released the drug into the stomach. Furthermore, blood samples were withdrawn periodically and rifabutin concentrations in the blood were determined by high performance liquid chromatography (HPLC). Data obtained in this study demonstrated that floating beads bearing rifabutin were capable of stomach specific delivery of drug for longer period with increased bioavailability compared to pure drug as well as with non-floating drug containing beads. Overall, gellan gum loaded floating beads have a promising potential to treat multidrug resistant Helicobacter pylori infection.
Keywords: Floating beads; Gellan gum; Helicobacter pylori; Rifabutin